2005
DOI: 10.1021/ac0481349
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in Situ Characterization of Surfaces Using Soft Landing in a Fourier Transform Ion Cyclotron Resonance Mass Spectrometer

Abstract: Mass-selected peptide ions produced by electrospray ionization were deposited onto fluorinated self-assembled monolayer surfaces (FSAM) surfaces by soft landing using a Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS) specially designed for studying interactions of large ions with surfaces. Analysis of the modified surface was performed in situ by combining 2-keV Cs+ secondary ion mass spectrometry with FT-ICR detection of the sputtered ions (FT-ICR-SIMS). Regardless of the initial charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
124
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(130 citation statements)
references
References 34 publications
4
124
0
Order By: Relevance
“…It should be noted that because SL of mass-selected ions produces highly pure uniform films on substrates it is difficult to compare our results with results obtained using conventional surface preparation methods. We have conducted extensive characterization of peptide films prepared using dried droplet and electrospray deposition approaches [11,12,21] and concluded that SIMS spectra obtained for such films are strongly affected by the presence of impurities and the morphology of the samples generated during the drying process. SIMS spectra obtained from peptide films prepared using these approaches are more complex than the corresponding spectra obtained from films prepared by SL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that because SL of mass-selected ions produces highly pure uniform films on substrates it is difficult to compare our results with results obtained using conventional surface preparation methods. We have conducted extensive characterization of peptide films prepared using dried droplet and electrospray deposition approaches [11,12,21] and concluded that SIMS spectra obtained for such films are strongly affected by the presence of impurities and the morphology of the samples generated during the drying process. SIMS spectra obtained from peptide films prepared using these approaches are more complex than the corresponding spectra obtained from films prepared by SL.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental approach for SL experiments has been described elsewhere [11,16]. Briefly, mass-selected peptide ions produced in a high-transmission electrospray source undergo normal-incidence collision with a SAM surface positioned at the rear trapping plate of the ICR cell.…”
Section: Methodsmentioning
confidence: 99%
“…It is normally assumed that the landed ion will retain its charge(s) but neutralization accompanying deposition/binding is also well known. Laskin has done much to elucidate the process of charge loss during and after the SL event [7]. The SL procedure not only alters the surface, but it also offers a new approach to preparative scale molecular separation and to molecular-level understanding of the interactions between molecules/ions and substrates relevant to biological, catalytic, and other applications [8,9].…”
mentioning
confidence: 99%
“…The first was a custom-built Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS) in which a beam of mass-selected ions of variable kinetic energy was used to modify surfaces via SL [7]. In situ analysis of the modified surfaces was achieved by 2 keV Cs ϩ secondary ion mass spectrometry (SIMS) with FT-ICR detection of the sputtered secondary ions (FT-ICR-SIMS).…”
mentioning
confidence: 99%
See 1 more Smart Citation